Theoretical Fundamentals of Atmospheric Optics - Timofeyev, Yu M.; Vasil'ev, A V (New Delhi: Viva Books, 2015)
The authors of this book present the theoretical fundamentals of atmospheric optics as a science of the propagation, transformation and generation in the atmosphere of electromagnetic radiation from the ultraviolet to microwave range of the spectrum. The main characteristics of the planets of the solar system and atmospheres are described. Special attention is given to the equation of transfer of radiation in different spectrum ranges; the absorption of radiation by atmospheric gases and aerosol, molecular, aerosol and different types of non-resonant scattering; atmospheric diffraction; reflection of radiation from the surface; and glow of the atmosphere. They present the method of calculating radiation for the solar and thermal ranges of the spectrum. The monograph will be of interest to experts working in the areas of the physics and optics of the atmosphere and also suitable for students and postgraduates studying the physics of atmosphere, meteorology, physical ecology and monitoring of the environment.
Appendix 447-470p.; References 471-476p.; Index 477-480p.
Keywords: Light scattering; radiation energetics; Atmospheric radiations